Assessment of the major odor contributors and health risks of volatile compounds in three disposal technologies for municipal solid waste. (15th May 2019) - Yao, Xing-Zhi; Ma, Ruo-Chan; Li, Hua-Jun; Wang, Chen; Zhang, Chi; Yin, Shan-Shan; Wu, Donglei; He, Xin-Yue; Wang, Jing; Zhan, Liang-Tong; He, Ruo
Graphical abstract: Highlights: Contribution of volatile compounds (VC) to odor from different waste treatments compared. Sulfur compounds were the main odor in the majority of MSW disposal facilities. Sorting system was an important emission site of VCs in MSW disposal plant. Breaks in HDPE cover and gas extraction wells resulted in emissions of VCs from landfill. MSW disposal facilities presented potential health risks for on-site workers. Abstract: Gaseous emissions from municipal solid waste (MSW) disposal plants pose serious odor pollution and health risks. In this study, the emission of volatile organic compounds and carbon disulfide was compared in the main processing units of three disposal methods, i.e., landfilling, eco-mechanical biological treatment (EMBT) and anaerobic fermentation in a MSW disposal plant. Among the detected volatile compounds (VCs), the top ten odor compounds were methanethiol, dimethyl sulfide, dimethyl disulfide, carbon disulfide, styrene, m-xylene, 4-ethyltoluene, ethylbenzene, 2-hexyl ketone and n-hexane in the MSW disposal plant. Sulfur compounds were the main source of odor at the majority of sampling sites, and aromatic compounds were the dominant odor substrates at the tipping unit and sorting system of EMBT, while 2-hexanone was the major odor substrate at the tipping unit (AT) and sorting system (AS) of anaerobic fermentation and the landfill working surface. At AS and AT, the lifetime cancer risk values for 1, 2-dichloroethane and trichloroethylene exceeded the carcinogenic risk value (>1.0E-04), and the hazard index values of naphthalene, trichloroethylene and acrolein all exceeded the acceptable level (>1). Therefore, special attention should be paid to VC emissions from MSW disposal facilities, and protection measures should be adopted for on-site workers to minimize health risks.